Distributed Fixed-Time Resource Allocation Algorithm for the General Linear Multi-Agent Systems - Shi, Xiasheng; Xu, Lei; Yang, Tao; Lin, Zhiyun; Wang, Xuesong (IEEE transactions on circuits and systems. II, Express briefs, 2022)
This brief focuses on the distributed resource allocation problem (RAP) for a general linear heterogeneous multi-agent system (MAS), in which each agent adopts different structure parameters. By means of multi-agent consensus approach and symbolic-function-based fixed-time control theory, an initialization-free distributed resource allocation algorithm is designed. Moreover, the equality constraint is solved based on the proportional-integral (PI) control idea and the output of all agents tracks to the optimal solution within fixed-time. Finally, we reveal the effectiveness and fast convergence performance of our proposed algorithm by a simulation example.